A Novel and Generic Workflow of Indocyanine Green Perfusion Assessment Integrating Standardization and Quantification Toward Clinical Implementation. Issue 6 (December 2021) - Noltes, Milou E.; Metman, Madelon J. H.; Heeman, Wido; Rotstein, Lorne; van Ginhoven, Tessa M.; Vriens, Menno R.; Engelsman, Anton F.; Boerma, E. Christiaan; Brouwers, Adrienne H.; van Dam, Gooitzen M.; Pasternak, Jesse D.; Kruijff, Schelto
Abstract : Objective: This study aims to generate a reproducible and generalizable Workflow model of ICG-angiography integrating Standardization and Quantification (WISQ) that can be applied uniformly within the surgical innovation realm independent of the user. Summary Background Data: Tissue perfusion based on indocyanine green (ICG)-angiography is a rapidly growing application in surgical innovation. Interpretation of results has been subjective and error-prone due to the lack of a standardized and quantitative ICG-workflow and analytical methodology. There is a clinical need for a more generic, reproducible, and quantitative ICG perfusion model for objective assessment of tissue perfusion. Methods: In this multicenter, proof-of-concept study, we present a generic and reproducible ICG-workflow integrating standardization and quantification for perfusion assessment. To evaluate our model's clinical feasibility and reproducibility, we assessed the viability of parathyroid glands after performing thyroidectomy. Biochemical hypoparathyroidism was used as the postoperative endpoint and its correlation with ICG quantification intraoperatively. Parathyroid gland is an ideal model as parathyroid function post-surgery is only affected by perfusion. Results: We show that visual subjective interpretation of ICG-angiography by experienced surgeons on parathyroid perfusion cannot reliably predict organ function impairment postoperatively, emphasizing the importance of an ICG quantification model. WISQ was able to standardize and quantify ICG-angiography and provided a robust and reproducible perfusion curve analysis. A low ingress slope of the perfusion curve combined with a compromised egress slope was indicative for parathyroid organ dysfunction in 100% of the cases. Conclusion: WISQ needs prospective validation in larger series and may eventually support clinical decision-making to predict and prevent postoperative organ function impairment in a large and varied surgical population. Abstract : Supplemental Digital Content is available in the text